Aerossacolitis and Pneumonia in an Indian Peafowl Caused by Lactobacillus agilis - Zitelli, Larissa Caló; Slaviero, Mônica; de Almeida, Bruno Albuquerque; de Carli, Silvia; da Silva, Emanoelly Machado Sousa; Volpato, Fabiana Caroline Zempulski; Barth, Afonso Luis; Pavarini, Saulo Petinatti; Siqueira, Franciele Maboni (Acta Scientiae Veterinariae, 2022)
Background: The peafowl is an ornamental bird that has the habit of eating directly from the earthy soil, which makes this bird more susceptible to endoparasites. One important endoparasite is Eucoleus contortus, which leads to inflammatory processes that alter the local microbiota, potentializing disease. By the other way, a member of the bird’s microbiota there is the genus Lactobacillus, but when occurs some imbalance, these bacteria can overgrowth and even cause some infection. This report describes the pathological and microbiological findings of chronic necrotizing pneumonia and aerossacolitis caused by Lactobacillus agilis in a peafowl, associated with parasitism by E. contortus. Case: A peafowl (Pavo cristatus), adult, male, who lived on a farm with contact with other species of animal, was submitted to post-mortem examination due to sudden death. This animal lived in an extensive system on the property and was the only one of its species. During the gross evaluation, the air sacs were filled with solid yellowish crumbly material. The same material was observed forming well-defined nodules that occupied > 50% of the lung parenchyma. Histological analysis showed multiple parabronchi dilated and filled with caseous necrosis, characterized by abundant cellular debris and fibrin deposition. These areas were surrounded by the proliferation of fibrous connective tissue and inflammatory infiltrate of macrophages, giant cells, lymphocytes, and plasma cells. The air sacs parenchyma showed fibrin deposition and mixed inflammatory infiltrate. Multiple gram-positive bacilli were observed within the caseous foci in Gram-stained slides. In the crop and esophageal mucosa, cross-sections of filiform nematodes morphologically compatible with E. contortus were associated with chronic inflammatory infiltrate and epidermal hyperkeratosis. A lung section was submitted to Gram-Brown-Hopps and Ziehl-Neelsen (ZN) stains for bacterial investigation, and Grocott’s methenamine silver (GMS) stain for fungal investigation. Short gram-positive bacilli bacteria are observed within the caseous foci in Gram-stained slides. By the other way, no agents were identified on the ZN and GMS stains. Following the analysis, lung fragments were cultivated at aerobic and microaerophilic conditions on sheep blood agar and McConkey agar. All the microbial cultures were incubated at 37°C to 48 h. Pure culture, in microaerophilic condition, of Gram-positive bacilli, was observed. The isolated bacterium was identified by MALDI-TOF MS as L. agilis. Discussion: Although uncommon, L. agilis was the single bacterium identified and therefore, associated as a primary cause of necrotic pneumonia and aerossacolitis in the studied peafowl. The presence of E. contortus could induce the aspiration of regurgitated of little amount of material from the gastrointestinal tract with sufficient bacterial load to initiate an infection, but not enough to smother the animal. The gradual aspiration can induce a chronic inflammatory condition. Infections by bacteria from the host microbiota have been observed in animals and humans with immunodeficiency. In summary, both the parasitosis and the inflammation could be resulted by the parasite and the aspiration of gastric product, which probably interfered in the immune response and allowed the overgrowth of L. agilis. In the current case report, based on macroscopic, microscopic and bacteriological results, we have provided insights to understand how the parasitosis made possible a pneumonia from a bacterium from the host’s microbiota. Finally, to the best of our knowledge, this is the first report of L. agilis as causal agent of fatal necrotic pneumonia and aerossacolitis in peafowl. Keywords: respiratory infection, ornamental birds, secondary infection, parasitosis.